PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Terhadap Karyawan PT. BPR Artha Mukti Santosa Semarang) - Nines Intan Novianti; Naili Farida; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
The existence and achievement of an organization while gaining its goal is cannot be divorced from human resource factor. The aim of this research is to find out the influence of organizational culture and work motivation toward employee's performance through job satisfaction. The type of this research is explanatory research, while the techniques of collecting data are questionnaire and interview. The amount of sample in this research is sixty six respondents with sampling census technique. Likert Scale is used as measuring scale, The technique of quantitative analysis uses validity test, reliability test, correlation coefficient, simple and multiple regression analysis, determination coefficient, significance test (t test and F test), and path analysis. The result of this research shows that organizational culture (X1) and work motivation (X2), whether simultaneously or partially, influencing job satisfaction (Z) and employee's performance (Y). Based on path analysis result, the direct influence of organizational culture or work motivation toward employee's performance are bigger than indirect influence through job satisfaction. Based on these results, it is suggested that the company should improve the organizational culture including increasing employee motivation and giving reward to the employee in the form of direct honour of superiors, so that they can be proud of their work and encourage them to work more optimally.